"ANALYSIS OF VITAL STATISTICS AND POPULATION FORECAST IN IRAN" - M Sotudeh Zand; H Khazaneh (Tehran University of Medical Sciences, 1971)
This investigation, with the help of present statistics and demographic techniques, deals with the status and quality of bio-incidence, as the basis for recognition of the national population. The study considers mortality, fertility, population growth and forecast. Calculations showed that mortality for men and women was 17.4 per 1000, in the year of this study (1966) and life expectancy, at the time of birth, was 47 years and 11 months for men, and 47 years and 6 months for women. Birth rate, for the same year, was found to be 48 per 1000, which according to the basic general fertility rate was calculated to be 247.9 per 1000.The population forecast for Iran, considering three fertility theories, has been calculated to be 46 to 54 million in the year 1981.